The Oxford handbook of corporate governance - Wright, Mike, 1952- (Oxford : Oxford University Press, 2013)
Corporate governance remains a central area of concern to business and society, and this handbook constitutes the definitive source of academic research on this topic synthesizing international studies from economics, strategy international business, organizational behaviour entrepreneurship, business ethics, accounting, finance, and law.
Description based on print version record.
Keywords: Corporate governance